Programma: 1 november Misty in Roots; 2 november Noir Désir; 3 november Pop Will Eat Itself, Blaggers Ita, Headless Chickens; 4 november Thione Seck & Le Raam Daan; 5 november Dance arena
Programma: 1 november Misty in Roots; 2 november Noir Désir; 3 november Pop Will Eat Itself, Blaggers Ita, Headless Chickens; 4 november Thione Seck & Le Raam Daan; 5 november Dance arena.